Determinants of Cesarean Section Decision in Indonesia: A Systematic Review - Devy, Shrimarti Rukmini; Diah Indriani; Budi Prasetyo; Hari Basuki Notobroto; Lutfi Agus Salim; Muhammad Ardian Cahya Laksana; Nafiatus Sintya Deviatin (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2024)
Background: Cesarean section delivery should be chosen if there are certain medical indications. However, the trend of childbirth by cesarean section shows a high increase in Indonesia. Complications of childbirth after cesarean section are higher compared to normal childbirth, this condition can endanger the health and safety of the mother and baby. Aims: to determine the determinants of cesarean section decisions in Indonesia. Method: this study is a systematic review using PRISMA, a database search via Google Scholar, PubMed, and ScienceDirect, keywords are adjusted to the topic discussed. Results: 13 articles were reviewed that were relevant to the research topic. Determinants of cesarean section decisions are medical indication including age, parity, pregnancy complications (hypertension and pre-eclampsia), history of delivery (cesarean section history), and labor complications (premature rupture of membranes and fetal distress) and by choice (own request) including residence in urban areas and employment. Conclusion: Interventions such as education, counseling, and others using appropriate communication, information, and education media, cooperation, and collaboration with academics and nongovernment organizations are needed in carrying out interventions.